ANALISIS KINERJA KAWASAN METROPOLITAN SARBAGITA - ADI ERAWATI, NI MADE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 7 No 1 (2012))
Performance appraisal is a process of recording and measuring activities realization to achieve organization’s mission. This research aims to investigate performance of local governments embracing the metropolitan area of Sarbagita (Denpasar, Badung, Gianyar and Tabanan). The performance is viewed from several aspects, that are independence rate, effectivity rate, efficiency rate, and harmony rate. Results show that all areas indicate increases in financial independence in 2007 and 2008, while effectivity rate of local government revenue are all above 100 percent which means extremely effective. Even though the average of local government revenue growth was relatively high i.e 43 percent, the growth of Denpasar City was negative in 2007. Civil servants expenditure growth varied among the areas. The growth was above 100 percent in Badung and Gianyar, but it was below 35 percent in other areas. The civil servants expenditure growth of more than 100 percent in Badung and Gianyar was too high compared to local government revenue growth of 43 percent, moreover if it is compared to the low, even negative growth of public expenditure in 2007 and 2008.
Keywords: government performance, metropolitan area, independence, effectivity rate, efficiency rate, harmony rate